Charcoal in soils: A preliminary view - Teixeira, S. Rainho [UNESP]; Dixon, Joe B.; White, G. Norman; Newsom, Lee A. (Wiley, 2018)
Charcoal can persist in soils for centuries, even millennia. This chapter describes the high quality charcoal, which illustrates the properties needed to provide a source of information on the conditions that existed when the soil parent material was deposited and that may be useful to initiate reconstruction of the history of the soil and the associated biota. Controlled temperature experiments show that temperatures around 230°C appear to be critical during charcoal formation and will define some of its physical and chemical properties. The amount of material available for dating has been a limiting factor in the use of charcoal for radiometric dating. Charcoal can be used to date soils by radiocarbon dating and by accelerator mass spectrometry. The history of soil formation is closely linked to paleoecology and paleoclimatology since they address both biological and climatic soil forming factors.
Keywords: Accelerator mass spectrometry; Charcoal formation; Paleoclimatology; Paleoecology; Radiocarbon dating; Soils